Expression of Toll-like receptors in the cerebellum during pathogenesis of prion disease - Liao, Xiangyu; Zhu, Wufei; Liao, Xingyu; Liu, Wensen; Hou, Yiwei; Wan, Jiayu (Frontiers in Behavioral Neuroscience, 2024)
Prion diseases, such as scrapie, entail the accumulation of disease-specific prion protein (P rP Sc ) within the brain. Toll-like receptors (TLRs) are crucial components of the pattern recognition system. They recognize pathogen-associated molecular patterns (PAMPs) and play a central role in orchestrating host innate immune responses. The expression levels of Toll-like receptors (TLRs) in the central nervous system (CNS) were not well-defined. To establish a model of prion diseases in BALB/C mice, the 22L strain was employed. The features of the 22L strain were analyzed, and the cerebellum exhibited severe pathological changes. TLR1-13 levels in the cerebellum were measured using quantitative polymerase chain reaction (qPCR) at time points of 60, 90, 120, and the final end point (145 days post-infection). During the pathogenesis, the expression levels of Toll-like receptors (TLRs) 1, 2, 7, 8, and 9 increased in a time-dependent manner. This trend mirrored the expression patterns of P rP Sc (the pathological isoform of the prion protein) and GFAP (glial fibrillary acidic protein). Notably, at the end point, TLR1-13 levels were significantly elevated. Protein level of TLR7 and TLR9 showed increasing at the end point of the 22L-infected mice. A deeper understanding of the increased Toll-like receptors (TLRs) in prion diseases could shed light on their role in initiating immune responses at various stages during pathogenesis. This insight is particularly relevant when considering TLRs as potential therapeutic targets for prion diseases.